2011
DOI: 10.4061/2011/923250
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aryl Hydrocarbon Receptor and Crosstalk with Estrogen Receptor in Response of Breast Cancer Cells to the Novel Antitumor Agents Benzothiazoles and Aminoflavone

Abstract: Many estrogen-receptor- (ER-) expressing breast cancers become refractory to ER-based therapies. New antitumor drugs like aminoflavone (AF) and benzothiazoles (Bzs) have been developed and have exquisite antitumor activity in ER+MCF-7 and T47D cells and in a MCF-7 nude mouse model. ER(−) breast cancer cells like MDA-MB-231 are less susceptible. We previously found in MCF-7 cells that these drugs activate the aryl hydrocarbon receptor (AhR) via translocation to the nucleus, induction of AhR-specific DNA binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…The AhR-independency of AF sensitivity in MDA-MB-468 and Cal51 is in discrepancy with the finding that MCF7 cells are sensitive to AF while Ah R100 MCF7 cells are AF resistant. Previous studies had shown that Ah R100 cells exhibited diminished AhR protein levels, mRNA levels, and ability to induce AhR target genes, rendering the cell line resistant to AF [8,18,19]. The difference in AF sensitivity with regards to AhR levels and activity could be cell type specific.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AhR-independency of AF sensitivity in MDA-MB-468 and Cal51 is in discrepancy with the finding that MCF7 cells are sensitive to AF while Ah R100 MCF7 cells are AF resistant. Previous studies had shown that Ah R100 cells exhibited diminished AhR protein levels, mRNA levels, and ability to induce AhR target genes, rendering the cell line resistant to AF [8,18,19]. The difference in AF sensitivity with regards to AhR levels and activity could be cell type specific.…”
Section: Discussionmentioning
confidence: 99%
“…Because flavonoid compounds have been shown to bind the intracellular aryl hydrocarbon receptor (AhR) and activate the AhR signaling pathway, one suggestion to explain AF’s activity pattern is metabolic activation by the AhR and its target genes, specifically the 1A isoforms of cytochome P450 (CYP) enzymes [7,8,16,17]. An AhR-deficient clone of MCF7 that was generated by continuous exposure to 100nM benzo [a] pyrene for six to nine months (Ah R100 ) has been shown to be rendered resistant to AF [8,18,19]. Further, previous studies revealed that AF is metabolized by CYP1A1 and, to a lesser extent, 1A2 and 1B1, and that this metabolism produces hydroxylamine species [7,8,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AhR-mediated regulation of metabolism of polycyclic aromatic hydrocarbons (PAH) has been implicated in a variety of cancers [2], [3]. PAH-induced AhR activation increases the transcription of a variety of genes encoding phase I drug metabolizing enzymes, such as CYP1A1 and CYP1B1, and phase II drug metabolizing enzymes, such as glutathione-S-transferase A1 (GSTA1) and UDP glucuronosyl transferase 1A2 (UGT1A2).…”
Section: Introductionmentioning
confidence: 99%
“…Aminoflavone (AF, NSC686288, and AFP464, NSC 710464) is an anti‐tumor agent with proved efficacy in clinical trials for the treatment of ER+ breast cancer patients. This agent presents a unique mechanism of action activating the aryl hydrocarbon receptor (AhR) signaling pathway which has a crosstalk with the ER signaling pathway [Denison and Nagy, ; Callero and Loaiza‐Pérez, ]. In vitro studies have demonstrated that ER+ breast cancer cell lines and renal cancer cell lines are sensitive to AF [Loaiza‐Pérez et al, ,b; Callero et al, ].…”
mentioning
confidence: 99%